Average Error: 0.0 → 0.0
Time: 15.1s
Precision: 64
\[\frac{1}{\left(x - 1\right) - y}\]
\[\frac{1}{\left(x - 1\right) - y}\]
\frac{1}{\left(x - 1\right) - y}
\frac{1}{\left(x - 1\right) - y}
double f(double x, double y) {
        double r56788744 = 1.0;
        double r56788745 = x;
        double r56788746 = r56788745 - r56788744;
        double r56788747 = y;
        double r56788748 = r56788746 - r56788747;
        double r56788749 = r56788744 / r56788748;
        return r56788749;
}

double f(double x, double y) {
        double r56788750 = 1.0;
        double r56788751 = x;
        double r56788752 = r56788751 - r56788750;
        double r56788753 = y;
        double r56788754 = r56788752 - r56788753;
        double r56788755 = r56788750 / r56788754;
        return r56788755;
}

Error

Bits error versus x

Bits error versus y

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[\frac{1}{\left(x - 1\right) - y}\]
  2. Final simplification0.0

    \[\leadsto \frac{1}{\left(x - 1\right) - y}\]

Reproduce

herbie shell --seed 1 
(FPCore (x y)
  :name "1 / ((x - 1) - y)"
  (/ 1.0 (- (- x 1.0) y)))